Partitioning oxidative fuels during cold exposure in humans: muscle glycogen becomes dominant as shivering intensifies - Haman, François (Blackwell Science Inc, 2005)
The effects of changes in shivering intensity on the relative contributions of plasma glucose, muscle glycogen, lipids and proteins to total heat production are unclear in humans. The goals of this study were: (1) to determine whether plasma glucose starts playing a more prominent role as shivering intensifies, (2) to quantify overall changes in fuel use in relation to the severity of cold exposure, and (3) to establish whether the fuel selection pattern of shivering is different from the classic fuel selection pattern of exercise. Using a combination of indirect calorimetry and stable isotope methodology, fuel metabolism was monitored in non-acclimatized adult men exposed for 90 mins to 10°C (low-intensity shivering (L)) or 5°C (moderate-intensity shivering (M)). Results show that plasma glucose oxidation is strongly stimulated by moderate shivering (+122% from L to M), but the relative contribution of this pathway to total heat generation always remains minor (< 15% of total heat production). Instead, muscle glycogen is responsible for most of the increase in heat production between L and M. By itself, the increase in CHO oxidation is responsible for the 100 W increase in metabolic rate observed between L and M, because rates of lipid and protein oxidation remain constant. This high reliance on CHO is not compatible with the well known fuel selection pattern of exercise, when considering the relatively low metabolic rates elicited by shivering (∼30% [Image: see text] for M). We conclude that shivering and exercise of similar energy requirements appear to be supported by different fuel mixtures. Investigating the physiological mechanisms underlying why a muscle producing only heat (shivering), or significant movement (exercise), shows a different pattern of fuel selection at the same power output strikes us as a fascinating area for future research.